Penerapan Model Numbered Head Together (NHT) Untuk Meningkatkan Hasil Belajar IPA di SDK Wologeru - Agustina Maria Merdeka (Ekspektasi: Jurnal Pendidikan Ekonomi, 2022)
This research is a classroom action research that aims to improve science learning outcomes in class V SDK Wologeru students through the application of the NHT model. The subjects in this study were 11 students of the Wologeru SDK for the academic year 2020/2021, totaling 11 people. The data were taken by using test, observation and interview techniques. Data were analyzed with simple descriptive statistics and compared the completeness of each cycle. The results of the study prove that the NHT model can improve learning outcomes in two cycles.